2013
DOI: 10.5897/2013.5885
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrogen peroxide or gold nanoparticles in protoporphyrin IX mediated antimicrobial photodynamic therapy on Staphylococcus aureus

Abstract: Antimicrobial photodynamic therapy (APDT) has been considered to treat skin diseases infected by drug resistant microorganisms. In this work, attempts were made to study the effectiveness of APDT with protoporphyrin IX (PPIX) in the presence of gold nanoparticles (GNPs) or hydrogen peroxide (H 2 O 2 ) against the human bacterial pathogen, Staphylococcus aureus. To photoactivate the PPIX, xenon light source was used at 626 nm. The bactericidal effect was analyzed by standard plate counting method. Attempts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The increase in antibiotic resistance among different classes of gram‐positive and gram‐negative bacteria has led to research for substitute antimicrobial therapies. Many reports showed that antibiotic resistant pathogenic bacteria can be inactivated successfully with photodynamic therapy (PDT), which is known as antimicrobial photodynamic therapy (APDT) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in antibiotic resistance among different classes of gram‐positive and gram‐negative bacteria has led to research for substitute antimicrobial therapies. Many reports showed that antibiotic resistant pathogenic bacteria can be inactivated successfully with photodynamic therapy (PDT), which is known as antimicrobial photodynamic therapy (APDT) …”
Section: Introductionmentioning
confidence: 99%
“…Although PDT has been used for treatment of certain cancers, it is also considered for the treatment of some oral diseases such as root canal infections and oral candidiasis. Some applications of PDT at a less developed stage include treatments for arthritis, restenosis, psoriasis, Barretts's esophagus, and atherosclerosis . In addition, PDT is being used in dermatology for a broadrange of neoplastic, inflammatory, and infectious cutaneous conditions …”
Section: Introductionmentioning
confidence: 99%
“…The overall fluorescence from post-treated S.aureus and P. aeruginosa exhibited a significant reduction (P<0.005) in the intensity. The emission peak at 340 nm is attributed to the key amino acid, tryptophan which is present in the bacteria[43]. From the inset of Figs.…”
mentioning
confidence: 95%